Witness - Harrigan, Lynn (UnderCurrents: Journal of Critical Environmental Studies, 2006)
Driving down a country road elated by the sun’s warmth and rolling corn fields I glimpse an old woman shuffling down a gravel lane toward the roadside mailbox a red coat thrown over her housedress